Peran Keaktifan Hakim dalam Mekanisme Keadilan Restoratif Terhadap Terdakwa pada Perkara Tindak Pidana Narkotika Sebagai Penyalahguna Bagi Diri Sendiri - Sulfi Amalia; Moch. Ivan Fadhila; Suci Romadhani (Jurnal Hukum Caraka Justitia, 2026)
This study aims to understand and analyze the role of judges' activeness in implementing restorative justice mechanisms for Defendants who are drug abusers. This research is a normative legal research, with a statutory and conceptual approach. The type of data used is secondary data, while the legal materials consist of primary, secondary, and non-legal materials, with the data collection technique being a library study. The processing of legal materials is carried out using a systematization technique on the legal materials. The research results indicate that judges must play an active role in implementing the phrase 'victim recovery' in cases of Defendants as drug abusers, in which the restorative justice mechanism in these cases allows the Panel of Judges examining the case to summon investigators as officials who elevate a person to suspect status in the case. Thus, victim recovery in this context refers to the restoration of the situation for the Defendant himself. Although this mechanism does not solely halt the legal process, it can be a consideration for the Panel of Judges in deciding the case.